Taste disturbance in patients with advanced cancer: a scoping review of clinical features and complications - Davies, Andrew (My University, 2023)
Purpose: The purpose of this scoping review is to appraise the published literature on taste disturbance in patients with advanced cancer, with the specific objectives being to determine its prevalence, clinical features and complications. Methods: This scoping review was conducted using the recommended methodological framework. A detailed search of databases (Medline, Embase, CINAHL and PsycInfo) was conducted to identify eligible studies: eligible studies needed to include patients with advanced cancer and needed to include details of clinical features and/or complications of taste disturbance. Standard bibliographic/systematic review software was used to store the records and manage the review process, respectively. Results: Twenty-five studies were identified from the database searches. The studies identified included eight physical and/or psychological symptom studies, six symptom cluster studies, five oral symptom studies and six taste and/or smell specific studies. Detailed data is presented on the clinical features and complications of taste disturbance and on the symptom clusters involving taste disturbance in this cohort of patients. Conclusion: This scoping review identified a relatively small number of relevant studies involving a relatively small number of participants. Nevertheless, it confirms that taste disturbance is a common problem in patients with advanced cancer and is associated with significant morbidity because of the primary condition and the associated complications.
PUBLISHED
Keywords: Neoplasms; Palliative care; Taste; Taste disorders; Cancer; Palliative Medicine